German Heterosexual Women's Pornography Consumption and Sexual Behavior. (17th March 2017) - Sun, Chyng Feng; Wright, Paul; Steffen, Nicola
This study found that German heterosexual women's personal and partnered consumption of pornography were positively correlated with their desire to engage in or having previously engaged in submissive (but not dominant) sexual behaviors such as having their hair pulled, having their face ejaculated on, being spanked, choked, called names, slapped, and gagged. The association between women's partnered pornography consumption and submissive sexual behavior was strongest for women whose first exposure to pornography was at a young age. The findings also indicated that women's personal and partnered pornography consumption were uniquely related to their engagement in submissive sexual behavior. Public Health Significance Statement: This study suggests that greater exposure to pornography among heterosexual German women is associated with their desire to engage in or having previously engaged in submissive sexual behaviors but not dominant behaviors. This pattern of correlations aligns with sexual script theory and content analyses of dominance and submission and gender in pornography. It does not align with the perspective that measures of pornography consumption are simply proxies for factors such as a high sex drive or an adventurous approach to sex.